Influence of Psychological Contract Violation on Organizational Commitment and Intention to Leave - Hassan Jafri, Md. (Prabandhan: Indian Journal of Management, 2012)
The purpose of this study is to investigate the influence of two dimensions of psychological contract violation (transactional and relational) on three dimensions of organizational commitment (affective, normative and continuance commitment) and intention to leave on employees of the retail sector in India. Data were gathered from 80 executives, selected randomly, working in different retail chains in south Delhi (NCR). Correlation and regression analyses were employed to analyze the data. The results revealed that transactional psychological contract violation predicts continuance commitment whereas, the relational psychological contract violation predicts affective as well as continuance commitment significantly. Intention to leave was predicted by both the dimensions of psychological contract violation. The findings imply that retail industry needs to manage employees' perceived expectations properly, especially employee's relational contractual obligations, otherwise, perception of its violation can jeopardize employee's affective commitment, and this may affect their job performance. The findings also imply that management needs to take care of employees' expectations; otherwise, an organization should be ready to lose some of their performing employees.